The Price Elasticity of Liquor in the U.S. and a Simple Method of Determination - Simon, Julian L. (Econometrica, 1968)
Arc elasticity is estimated for liquor by simply comparing state sales before and after price increases, standardized by states in which price did not change. The technique can be used wherever there are several economic units independent with respect to price changes; it allows causal interpretation and it permits comparison of various length-of-run elasticities.